Electron stream effect in 0.35 Tesla magnetic resonance image guided radiotherapy for breast cancer - Lee, Hsin-Hua; Wang, Chun-Yen; Chen, Shan-Tzu; Lu, Tzu-Ying; Chiang, Cheng-Han; Huang, Ming-Yii; Huang, Chih-Jen (Frontiers in Oncology, 2023)
Purpose: This research aimed to analyze electron stream effect (ESE) during magnetic resonance image guided radiotherapy (MRgRT) for breast cancer patients on a MR-Linac (0.35 Tesla, 6MV), with a focus on the prevention of redundant radiation exposure. Materials and Methods: RANDO phantom was used with and without the breast attachment in order to represent the patients after breast conserving surgery (BCS) and those received modified radical mastectomy (MRM). The prescription dose is 40.05 Gy in fifteen fractions for whole breast irradiation (WBI) o 20 Gy single shot for partial breast irradiation (PBI). Thirteen different portals of intensity-modulated radiation therapy were created. And then we evaluated dose distribution in five areas (on the skin of the tip of the nose, the chin, the neck, the abdomen and the thyroid.) outside of the irradiated field with and without 0.35 Tesla. In addition, we added a piece of bolus with the thickness of 1cm on the skin in order to compare the ESE difference with and without a bolus. Lastly, we loaded two patients’ images for PBI comparison. Results: We found that 0.35 Tesla caused redundant doses to the skin of the chin and the neck as high as 9.79％ and 5.59％ of the presecription dose in the BCS RANDO model, respectively. For RANDO phantom without the breast accessory (simulating MRM), the maximal dose increase were 8.71% and 4.67% of the presecription dose to the chin and neck, respectively. Furthermore, the bolus we added efficiently decrease the unnecessary dose caused by ESE up to 59.8%. Conclusion: We report the first physical investigation on successful avoidance of superfluous doses from ESE on a 0.35T MR-Linac for breast cancer patients. Future studies of MRgRT on the individual body shape and its association with ESE influence is warranted.